2005
DOI: 10.1084/jem.20041212
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of UV radiation–induced immunosuppression by IL-12 is dependent on DNA repair

Abstract: The immunostimulatory cytokine IL-12 is able to antagonize immunosuppression induced by solar/ultraviolet (UV) radiation via yet unknown mechanisms. IL-12 was recently found to induce deoxyribonucleic acid (DNA) repair. UV-induced DNA damage is an important molecular trigger for UV-mediated immunosuppression. Thus, we initiated studies into immune restoration by IL-12 to discern whether its effects are linked to DNA repair. IL-12 prevented both UV-induced suppression of the induction of contact hypersensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
2
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(180 citation statements)
references
References 27 publications
7
168
2
3
Order By: Relevance
“…26 Ghoreishi et al 27 observed that regulatory T cells expanded by vitamin D 3 can only inhibit ova-specific CD8 T cells in a local, not a systemic, model. In addition, regulatory T cells may require stimulation by CPD DNA-damaged Langerhans cells migrating into sDLNs, 28 whereas this study found no requirement of CPD formation as a trigger for UVB-induced immunosuppression. Instead, it is possible that other suppressor cell types, such as UVB-induced suppressor B cells, could be indirectly inhibiting the responses of ova-specific CD8 T cells by interfering with Ag presentation in secondary lymphoid organs.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…26 Ghoreishi et al 27 observed that regulatory T cells expanded by vitamin D 3 can only inhibit ova-specific CD8 T cells in a local, not a systemic, model. In addition, regulatory T cells may require stimulation by CPD DNA-damaged Langerhans cells migrating into sDLNs, 28 whereas this study found no requirement of CPD formation as a trigger for UVB-induced immunosuppression. Instead, it is possible that other suppressor cell types, such as UVB-induced suppressor B cells, could be indirectly inhibiting the responses of ova-specific CD8 T cells by interfering with Ag presentation in secondary lymphoid organs.…”
Section: Discussioncontrasting
confidence: 74%
“…27 Modulation of skin dendritic cells by vitamin D 3 is proposed to be important in this process; however, these cells are also prone to UVBinduced CPD. 28 Skin dendritic cells take up exogenous Ag, which they then process and present to CD4 T cells in sDLNs. To an extent, they can also cross present to CD8 T cells; however, stimulation of CD8 T cells mostly occurs after Ag transfer to CD8␣ ϩ dendritic cells in secondary lymphoid organs, which then cross present to CD8 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 is also able to antagonize UV-induced immunosuppression (18 -20). This activity also appears to be related to the effect of IL-12 on DNA repair because IL-12 prevented both UV-induced suppression of the induction of contact hypersensitivity (CHS) and the depletion of Langerhans cells, the primary APC of the skin, in WT mice but not in DNA repair-deficient mice (21). Thus, these findings identified a new mechanism by which IL-12 can restore immune responses and also demonstrated a link between DNA repair and the prevention of UV-induced immunosuppression by IL-12.…”
Section: Il-18mentioning
confidence: 99%
“…8 Unfortunately, the exact mechanism by which UV modulates inflammation and immunity is not completely understood, even though understanding these events could lead to the design of novel immune-modulating treatment regimes. UV-induced DNA damage, 9 together with the production of oxidized lipids 10 and the release of immune-modulating cytokines (particularly prostaglandin E 2 , IL-4, and IL-10 11,12 ) play important roles. The downstream cellular targets of these UV-induced inflammatory mediators include dendritic cells, 13 dermal mast cells, 12 as well as regulatory T 14 and B cells.…”
mentioning
confidence: 99%